Testing, Monitoring and Diagnostic of High Voltage Equipment - Zhang, Zhijin; Zheng, Hualong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reliability of high-voltage equipment is critical to the safe operation of the power grid. This reprint focuses on the new developments and advances in both fundamental and applied research on the testing, monitoring, and diagnostics of high-voltage equipment, including insulators, transformers, etc.